A kind of building coating and its preparation method and use method
By adding metakaolin and hydrated lime to dihydrate gypsum, the hydration reaction is promoted to generate water-resistant and bonding water insoluble matter, which solves the problem that dihydrate gypsum is easy to soften in humid environments, and realizes a high-strength, water-resistant coating structure, extends service life and reduces costs.
Patent Information
- Application Number
- CN202310732348.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-06-20
AI Technical Summary
It is difficult to use dihydrate gypsum as a bonding film forming agent for coatings in the prior art, and gypsum products are prone to absorb water and soften in humid or immersed environments, resulting in a decrease in strength and limited application range.
By adding metakaolin and hydrated lime to dihydrated gypsum, a coupling reaction occurs under the action of water to generate water insoluble substances such as ettringite, hydrated calcium silicate gel and water calcium zeolite with adhesion, water resistance and micro-expansion properties, forming a high-strength, water-resistant coating structure.
The bonding and film forming function of dihydrate gypsum is realized, which improves the water resistance and strength of the coating, extends the service life, and reduces production costs.
Smart Images

Figure BDA0004294597690000081 
Figure BDA0004294597690000091 
Figure BDA0004294597690000092
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation and application of architectural coatings, and in particular to an architectural coating and a preparation method and a use method thereof. Background Art
[0002] Gypsum is an industrial raw material and building material with abundant reserves and wide applications. Gypsum building materials have the characteristics of fire resistance, heat insulation, sound insulation, flame retardancy, impact resistance, good volume stability, strong bonding, frost resistance, no hollowing and cracking, etc. They also have the function of "breathing" and regulate the indoor air humidity. They are currently environmentally friendly building materials that have attracted much attention. In addition, gypsum also has a strong hiding power. When used in large quantities, the paint can achieve excellent hiding performance by using less or no expensive titanium dioxide. The solubility of dihydrate gypsum (CaSO4·2H2O) at 20°C is 2.04g / L, and the solubility of α-hemihydrate gypsum (CaSO4·0.5H2O) is as high as 6.20g / L. Since dihydrate gypsum is easily soluble and has no gelling properties, it cannot be used alone as a binder and film-forming agent for paint. The current method of use generally requires calcination, grinding and other processes to obtain gelling hemihydrate gypsum, that is, building gypsum. Due to the high solubility of gypsum, gypsum products easily absorb water and soften in a humid or water-soaked environment, resulting in a significant drop in strength, compression deformation and surface peeling, which greatly limits its scope of application.
[0003] At present, the main method to improve the water resistance of gypsum is to use gypsum and organic matter to achieve the purpose of waterproofing. For example, Ma Hongen modified silane styrene acrylic emulsion in the study of the waterproof performance of gypsum and its composite materials. By adding 0.1% of modified silane styrene acrylic emulsion to gypsum, the softening coefficient was increased by 148% and the water absorption rate was reduced by 33% compared with the blank group. ("Synthesis of Silane Modified Styrene Acrylic Emulsion and Research on the Effect of Composite Mineral Materials on the Waterproof Performance of Desulfurized Gypsum", Ma Hongen, Master's Thesis, Jiangsu University, 2019). However, since the added organic matter will age and degrade over time and lose its waterproof effect, the service life of the product obtained by combining gypsum and organic matter is limited and cannot provide long-term waterproof protection. The volatilization of organic matter in the composite material is more harmful to human health. Therefore, the use of inorganic internal waterproofing is the current mainstream method. Adding volcanic ash active substances to gypsum can increase the softening coefficient of gypsum and reduce water absorption.
[0004] The dispersion medium of solvent-based paint is organic solvent, and the emission of volatile organic compounds (VOC) is relatively high, so water-based powder environmentally friendly paint has become the trend of paint development. At present, most water-based paints on the market use water as solvent. Although the use of volatile organic solvents has been greatly reduced, its disadvantages are obvious, mainly manifested in: large volume and weight, high packaging and storage requirements, good sealing, so the packaging and transportation costs are high, which invisibly increases the cost of paint.
[0005] Inorganic powder coatings can save costs in packaging. When using, just add water and stir evenly. It is easy to use and has certain competitive advantages in terms of price. In addition, inorganic powder coatings can react with the base material to form a hydration reaction, so that the coating and the building are integrated. It has strong adhesion, excellent weather resistance and anti-aging ability, so the service life of inorganic powder coatings is the same as that of the building. In addition, inorganic powder architectural coatings are highly alkaline, which is not conducive to the growth of bacteria and other microorganisms. Therefore, they have excellent mildew resistance and are a green, healthy and environmentally friendly coating.
[0006] There are also reports on the preparation of inorganic dry powder coatings using semi-hydrated gypsum and anhydrous gypsum as raw materials. For example, in the authorized invention patent application with publication number CN102173710B, a certain amount of active volcanic ash materials such as cement or slag are added to anhydrous hard gypsum and semi-hydrated gypsum to improve the mechanical properties and waterproof properties of the coating. However, anhydrous hard gypsum and semi-hydrated gypsum are obtained by high-temperature calcination and dehydration of dihydrate gypsum. The hydration rate of semi-hydrated gypsum is too fast, and the coating can be operated for a short time, which is not conducive to construction. The added cement also needs high-temperature calcination, and the energy consumption of the process is too large, which is inconsistent with the low-carbon environmental protection policy advocated by my country. Therefore, the use of anhydrous gypsum and semi-hydrated gypsum as raw materials to prepare inorganic dry powder coatings has obvious defects.
[0007] So far, there is no report on the direct use of dihydrate gypsum as a coating adhesive film-forming agent. The key to the problem is how to make dihydrate gypsum have adhesive, water-resistant and micro-expansion crack resistance properties so that it can play its adhesive film-forming function and be used in architectural coatings.
[0008] Therefore, after long-term experimental research and investigation, the present invention team provides a dihydrate gypsum-based water-resistant and crack-resistant inorganic powder type building coating, which uses dihydrate gypsum as the basic raw material, and adds kaolin and slaked lime at the same time. Under the action of water, dihydrate gypsum reacts with kaolin and slaked lime to generate water-insoluble substances such as calcium aluminate, hydrated calcium silicate gel and calcium zeolite with good adhesion, water resistance and micro-expansion properties. The product is shown in Figure 1 ; As the reaction proceeds, these stable hydrate crystals continue to grow, and at the same time, ettringite and zeolite crystals and hydrated calcium silicate gel are continuously precipitated from the solution and fill the space in the structure. Relying on multiple interaction forces, the cementitious materials are bonded together to form a tight water-resistant structure; the unreacted dihydrate gypsum crystals and fillers serve as the skeleton of the coating structure, ettringite and zeolite serve as water-resistant substances to fill between the skeletons, and the hydrated calcium silicate gel material wraps and bonds the skeleton and the filling material into a whole, so that the skeleton, water-insoluble substances and cementitious materials are effectively bonded to form a high-strength and water-resistant integrated structure. The structure is shown in FIG. Figure 2. The gelling material wraps the dihydrate inside, blocking the water from entering and contacting the internal dihydrate gypsum, slowing down the diffusion of water in the material, and effectively improving the strength and water resistance of the coating. Therefore, the dihydrate gypsum is used as an inorganic film-forming binder and filler for the coating. A small amount of water-dispersible or water-soluble organic polymer auxiliary film-forming agent is added to the formula. The polymer auxiliary film-forming agent improves the surface performance of the coating, which is beneficial to improving the toughness of the coating and the deformation of the coating. The SEM image of the coating surface without the addition of organic polymer auxiliary film-forming agent is shown in Figure 3 , the SEM image of the coating surface with polyvinyl alcohol added is shown in Figure 4 . Summary of the invention
[0009] The present application aims to provide a building coating and a method for preparing and using the same, and in particular to provide a dihydrate gypsum-based water-resistant and crack-resistant inorganic powder-type building coating whose main characteristics are water resistance, crack resistance, antibacterial, long life, low carbon and environmental protection.
[0010] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0011] The architectural coating of the present invention comprises the following raw materials by weight: 20-70 parts of dihydrate gypsum, 5-50 parts of metakaolin, 5-35 parts of slaked lime, 1-5 parts of polymer auxiliary film-forming agent, 1-30 parts of filler, 0.1-0.5 parts of high-efficiency water reducing agent, 0.1-0.5 parts of defoaming agent, 0.1-0.5 parts of dispersant, 0.1-0.5 parts of leveling agent, 0.1-0.5 parts of anti-sagging agent and 0.1-0.5 parts of water retaining agent.
[0012] Preferably, the following raw materials are included by weight: 20-50 parts of dihydrate gypsum, 15-30 parts of metakaolin, 15-30 parts of slaked lime, 2-4 parts of polymer auxiliary film-forming agent, 5-26 parts of filler, 0.1-0.3 parts of high-efficiency water reducing agent, 0.1-0.3 parts of defoaming agent, 0.1-0.3 parts of dispersant, 0.1-0.3 parts of leveling agent, 0.1-0.2 parts of anti-sagging agent, and 0.1-0.2 parts of water retaining agent.
[0013] Further preferably, the following raw materials are included by weight: 35 parts of dihydrate gypsum, 19 parts of metakaolin, 22 parts of slaked lime, 3 parts of polymer auxiliary film-forming agent, 20 parts of filler, 0.2 parts of high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retaining agent.
[0014] The dihydrate gypsum is preferably dihydrate gypsum with a purity greater than 90%, a composition of CaSO4·2H2O, a whiteness of ≥80%, a fineness of ≥300 meshes, and a moisture content of ≤1.5%.
[0015] The metakaolin is preferably kaolin calcined at 600-900°C, with a whiteness of ≥80%, a fineness of ≥500 mesh, and a moisture content of ≤1.5%.
[0016] The slaked lime is preferably calcium hydroxide with a purity of ≥90%, a whiteness of ≥80%, a fineness of ≥600 meshes, and a moisture content of ≤1.5%.
[0017] The polymer auxiliary film-forming agent of the present invention comprises one or more composite powders of water-soluble ethylene / vinyl acetate redispersible latex powder, polyacrylate redispersible latex powder and water-soluble polyvinyl alcohol, with a fineness of ≥100 mesh and a moisture content of ≤2.0%.
[0018] The high-efficiency water reducer described in the present invention is a polycarboxylic acid high-efficiency water reducer.
[0019] The filler of the present invention is one or a combination of two or more of quartz powder, talcum powder, wollastonite powder, sericite powder, heavy calcium carbonate powder or diatomaceous earth powder, preferably quartz powder, with whiteness ≥80%, fineness ≥500 mesh, and moisture content ≤1.5%.
[0020] The preparation method of the present invention is as follows: weigh the formulated amount of dihydrate gypsum, metakaolin, slaked lime, polymer auxiliary film-forming agent, filler, high-efficiency water reducer, defoamer, dispersant, leveling agent, anti-sagging agent and water-retaining agent and mix them evenly.
[0021] The method of use of the present invention is: add an appropriate amount of clean water to the dry powder, apply 4 cups of slurry with a viscosity of 14-18s, stir evenly until there are no particles, and then use it for brushing, rolling, spraying, and reach a suitable thickness.
[0022] The specific preparation and use process is as follows: weigh the mass of each component of the raw material according to the mass fraction, stir and mix well, and then seal it in moisture-proof packaging, store it dry, or use it immediately. When using, add an appropriate amount of clean water to the powder coating and mix it evenly, and control the viscosity of the slurry to 14-18s after applying 4 cups. Before coating, the wall base should be plastered and leveled in advance, and it is best to apply a layer of waterproof and alkali-resistant agent first. When coating, ensure that the minimum ambient temperature is above 5°C, wet the wall with clean water, and then brush, roll or spray it. It can be applied 1-3 times as needed. After coating in dry areas, it is best to spray with clean water on the third and seventh days for moisturizing and maintenance, which is beneficial to the strength development of the coating.
[0023] According to actual needs, the architectural coating may further contain: 0-10 parts of pigment.
[0024] The above-mentioned pigments are preferably organic alkali-resistant pigments or inorganic alkali-resistant pigments with a fineness of ≥500 mesh, such as ultramarine blue, iron oxide red powder, etc.
[0025] The defoamer of the present invention is preferably a powder defoamer with a fineness of ≥200 mesh, such as polyether modified silicon.
[0026] The dispersant of the present invention is preferably a powder dispersant with a fineness of ≥200 mesh, such as polyethylene oxide.
[0027] The anti-sagging agent of the present invention is preferably a powder anti-sagging agent with a fineness of ≥200 mesh, such as polyamide wax powder.
[0028] The water reducer of the present invention is preferably a powder-type high-efficiency water reducer with a fineness of ≥200 mesh, such as a polycarboxylic acid high-efficiency water reducer.
[0029] The water-retaining agent of the present invention is preferably a powdered water-retaining agent with a fineness of ≥200 mesh, such as hydroxypropyl methylcellulose.
[0030] Beneficial effects of the present invention:
[0031] 1. The present invention uses dihydrate gypsum as the basic raw material to prepare the coating, and tests are carried out according to the relevant technical indicators and test methods of "Inorganic Dry Powder Architectural Coatings" (JG / T445-2014). The results are as follows: 1) The coating surface is flat and smooth; 2) Water resistance, alkali resistance, temperature change resistance, and artificial aging resistance are normal; 3) The surface drying time is 1.25h, which is within the indicator of 2h; the contrast ratio is 0.96, which is greater than 0.90; the scrub resistance is greater than 2000, and the stain resistance is 10.89%, which is less than 15%. All price indicators meet the standards; 4) The appearance of the paint is intact, without any powdering, discoloration or cracking; 5) The pH value of the paint slurry is 12, which is greater than 10, so there is no need to add antibacterial agents, and it also has antibacterial effects, and will not mold or discolor when used on exterior walls; 6) The whiteness is 86.66, which has a high whiteness and strong hiding power. Therefore, the paint can replace titanium dioxide pigment to achieve the effect of improving the whiteness of the paint and reducing the use of titanium dioxide. There is no need to add titanium dioxide. Titanium dioxide is expensive, and reducing its use can reduce the production cost of the paint.
[0032] 2. The present invention adds a small amount of water-dispersible or water-soluble organic polymer auxiliary film-forming agent, so that the formed film has a barrier function, which helps to reduce the potential alkali efflorescence of the coating and makes the coating have excellent surface performance; the polymer auxiliary film-forming agent polyvinyl alcohol added in the formula of the present invention improves the surface performance of the coating, which is conducive to improving the toughness of the coating and improving the deformability of the coating; the addition of fillers can adjust the expansion rate, scrub resistance and other properties of the coating, among which the coarse particle filler can also create the texture of the coating and improve the decorative performance of the coating. Under the joint action of other necessary admixtures, a healthy and environmentally friendly architectural coating with water resistance, high adhesion, crack resistance, long life, excellent appearance performance and alkaline antibacterial is obtained.
[0033] 3. The main raw materials of the present invention are derived from natural minerals, the production process is simple, the energy consumption is low, and the amount of high-cost components such as organic components and titanium dioxide added is low or not used, so the cost can be controlled at a low level.
[0034] 4. The architectural coating prepared by the method of the present invention has excellent performance, and is excellent in texture, adhesion, water resistance, alkali resistance, etc., and has high economic, environmental protection and social benefits; the coating is in powder form, has a long shelf life, is easy to use, and can be used by adding water and stirring evenly, which is in line with the future development trend of green and healthy architectural coatings; at the same time, due to the simple packaging and convenient transportation process, the packaging and transportation costs are greatly reduced, it has performance and price advantages, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the XRD spectrum of the hydration reaction product of dihydrate gypsum, metakaolin and slaked lime.
[0036] Figure 2 This is the SEM spectrum of the hydration reaction products of dihydrate gypsum, metakaolin and slaked lime.
[0037] Figure 3 SEM images of the surfaces of dihydrate gypsum, metakaolin, slaked lime and filler coatings.
[0038] Figure 4 SEM images of the surfaces of dihydrate gypsum, metakaolin, slaked lime, filler and polyvinyl alcohol coating. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the examples. However, these examples shall not be interpreted as limiting the scope of protection of the present invention. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the instructions for use of the products.
[0040] The water reducer in the embodiment of the present application is a polycarboxylic acid high-efficiency water reducer produced by Guangdong Wengjiang Chemical Reagent Co., Ltd., the defoamer is AGITAN P803 powder defoamer produced by MUNZING-CHEMIE of Germany, the dispersant is POLYOX TMWSR N-60K dispersant produced by DowChemical Company, the leveling agent is BYK345 leveling agent produced by BYK of Germany, the anti-sagging agent is polyamide wax powder produced by ARKEMA of France, and the water retaining agent is hydroxypropyl methylcellulose produced by Shandong Yousuo Chemical Technology Co., Ltd.
[0041] Example 1
[0042] Raw material ratio: 35 parts of dihydrate gypsum, 19 parts of metakaolin, 22 parts of slaked lime, 3 parts of polyvinyl alcohol, 20 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0043] Weigh the raw materials of the above components, stir them evenly in a stirrer, and then seal them in moisture-proof packaging to prepare coating 1. Store in a dry and closed environment. When using, add an appropriate amount of clean water to the dry powder, the viscosity of the slurry is 14-18s after 4 cups of coating, stir evenly until there are no particles, and then use it for brushing, rolling, spraying, and reach a suitable thickness.
[0044] Example 2
[0045] Raw material ratio: 20 parts of dihydrate gypsum, 25 parts of metakaolin, 25 parts of slaked lime, 3 parts of polyvinyl alcohol, 26 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0046] Weigh the raw materials of the above components, stir them evenly in a stirrer, and then seal them in moisture-proof packaging to prepare coating 2. Store in a dry and closed environment. When using, add an appropriate amount of clean water to the dry powder, the viscosity of the slurry is 14-18s after 4 cups of coating, stir evenly until there are no particles, and then use it for brushing, rolling, spraying, and reach a suitable thickness.
[0047] Example 3
[0048] Raw material ratio: 50 parts of dihydrate gypsum, 19 parts of metakaolin, 22 parts of slaked lime, 3 parts of polyvinyl alcohol, 5 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0049] Weigh the raw materials of the above components, stir them evenly in a stirrer, and then seal them in moisture-proof packaging to prepare coating 3. Store in a dry and closed environment. When using, add an appropriate amount of clean water to the dry powder, the viscosity of the slurry is 14-18s after 4 cups of coating, stir evenly until there are no particles, and then use it for brushing, rolling, spraying, and reach a suitable thickness.
[0050] Example 4
[0051] Raw material ratio: 35 parts of dihydrate gypsum, 15 parts of metakaolin, 25 parts of slaked lime, 3 parts of polyvinyl alcohol, 21 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0052] Weigh the raw materials of the above components, stir them evenly in a stirrer, and then seal them in moisture-proof packaging to prepare coating 4. Store in a dry and closed environment. When using, add an appropriate amount of clean water to the dry powder, the viscosity of the slurry is 14-18s, stir evenly until there are no particles, and then use it for brushing, rolling, spraying, and reach a suitable thickness.
[0053] Example 5
[0054] Raw material ratio: 35 parts of dihydrate gypsum, 30 parts of metakaolin, 25 parts of slaked lime, 3 parts of polyvinyl alcohol, 6 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0055] Weigh the raw materials of the above components, stir them evenly in a stirrer, and then seal them in moisture-proof packaging to prepare coating 5. Store in a dry and closed environment. When using, add an appropriate amount of clean water to the dry powder, the viscosity of the slurry is 14-18s after 4 cups of coating, stir evenly until there are no particles, and then use it for brushing, rolling, spraying, and reach a suitable thickness.
[0056] Example 6
[0057] Raw material ratio: 35 parts of dihydrate gypsum, 22 parts of metakaolin, 15 parts of slaked lime, 3 parts of polyvinyl alcohol, 24 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0058] Weigh the raw materials of the above components, stir them evenly in a stirrer, and then seal them in moisture-proof packaging to prepare coating 6. Store in a dry and closed environment. When using, add an appropriate amount of clean water to the dry powder, the viscosity of the slurry is 14-18s after 4 cups of coating, stir evenly until there are no particles, and then use it for brushing, rolling, spraying, and reach a suitable thickness.
[0059] Example 7
[0060] Raw material ratio: 35 parts of dihydrate gypsum, 26 parts of metakaolin, 30 parts of slaked lime, 3 parts of polyvinyl alcohol, 5 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0061] Weigh the raw materials of the above components, stir them evenly in a stirrer, and then seal them in moisture-proof packaging to prepare coating 7. Store in a dry and closed environment. When using, add an appropriate amount of clean water to the dry powder, the viscosity of the slurry is 14-18s after 4 cups of coating, stir evenly until there are no particles, and then use it for brushing, rolling, spraying, and reach a suitable thickness.
[0062] Example 8
[0063] Raw material ratio: 35 parts of dihydrate gypsum, 19 parts of metakaolin, 22 parts of slaked lime, 3 parts of polyvinyl alcohol, 10 parts of quartz powder, 10 parts of ultramarine, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0064] Weigh the raw materials of the above components, stir them evenly in a stirrer, and then seal them in moisture-proof packaging to prepare coating 8. Store in a dry and closed environment. When using, add an appropriate amount of clean water to the dry powder, the viscosity of the slurry is 14-18s after 4 cups of coating, stir evenly until there are no particles, and then use it for brushing, rolling, spraying, and reach a suitable thickness.
[0065] In order to further verify the feasibility and effectiveness of the present invention and screen out the best solution, the inventor conducted a series of experiments, as follows:
[0066] 1. Experimental Methods
[0067] 1. Technical indicators and test methods of coatings
[0068] According to the relevant technical indicators and test methods of "Inorganic Dry Powder Architectural Coatings" (JG / T 445-2014), the specific test items include: workability, coating appearance, flexibility, water resistance, alkali resistance, scrub resistance, temperature change resistance, stain resistance, resistance to artificial weathering, whiteness and pH. The test items and test standards / methods are as follows:
[0069] For construction performance, operability time and appearance test methods, refer to GB / T 9779-2015;
[0070] Drying time (surface drying) test method, refer to GB / T 1728;
[0071] Contrast ratio test method, refer to GB / T 23981;
[0072] Flexibility test method, refer to GB / T 1748;
[0073] Water resistance test method, refer to GB / T 1733;
[0074] Alkali resistance test method, refer to GB / T 9265;
[0075] The test method for scrub resistance is in accordance with GB / T 9266;
[0076] Temperature resistance test method, refer to GB / T9779;
[0077] The stain resistance test method refers to GB / T 9780;
[0078] Test method for resistance to artificial weathering, refer to GB / T 1865;
[0079] See Table 1-Table 2. Table 1 shows the technical performance requirements for inorganic dry powder exterior wall coatings in "Inorganic Dry Powder Architectural Coatings" (JG / T 445-2014). Table 2 shows the technical performance requirements for inorganic dry powder interior wall coatings in "Inorganic Dry Powder Architectural Coatings" (JG / T 445-2014).
[0080] Table 1 Technical performance requirements of inorganic dry powder exterior wall coatings
[0081]
[0082]
[0083] Table 2 Technical performance requirements of inorganic dry powder interior wall coatings
[0084]
[0085] 2 Test 1
[0086] 2.1 Raw material selection test, set up 7 recipes, the specific scheme is as follows:
[0087] Formula 1 - "Dihydrate gypsum is used as raw material"
[0088] Raw material ratio: 35 parts of dihydrate gypsum, 19 parts of metakaolin, 22 parts of slaked lime, 3 parts of polyvinyl alcohol, 20 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0089] Formula 2 - "No dihydrate gypsum is used in the raw materials"
[0090] Raw material ratio: 25 parts of metakaolin, 25 parts of slaked lime, 3 parts of polyvinyl alcohol, 46 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retaining agent.
[0091] Recipe 3 - "Use hemihydrate gypsum instead of dihydrate gypsum"
[0092] Raw material ratio: 35 parts of hemihydrate gypsum, 19 parts of metakaolin, 22 parts of slaked lime, 3 parts of polyvinyl alcohol, 20 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0093] Recipe 4 - "Use anhydrous gypsum instead of dihydrate gypsum"
[0094] Raw material ratio: 35 parts of anhydrous gypsum, 19 parts of metakaolin, 22 parts of slaked lime, 3 parts of polyvinyl alcohol, 20 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0095] Recipe 5: "No slaked lime used in the raw materials"
[0096] Raw material ratio: 45 parts of dihydrate gypsum, 30 parts of metakaolin, 3 parts of polyvinyl alcohol, 21 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0097] Recipe 6: "No kaolin used in the raw materials"
[0098] Raw material ratio: 45 parts of dihydrate gypsum, 30 parts of slaked lime, 3 parts of polyvinyl alcohol, 21 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0099] See Table 3.
[0100] Table 3 Coating formula screening table
[0101] raw material Recipe 1 Recipe 2 Recipe 3 Recipe 4 Recipe 5 Recipe 6 Gypsum dihydrate(g) 35 45 45 Metakaolin(g) 19 25 19 19 30 Slaked lime(g) 22 25 22 22 30 Polyvinyl alcohol (g) 3 3 3 3 3 3 Quartz powder(g) 20 46 20 20 21 21 Polycarboxylate high efficiency water reducing agent (g) 0.2 0.2 0.2 0.2 0.2 0.2 Defoaming agent(g) 0.2 0.2 0.2 0.2 0.2 0.2 Dispersant(g) 0.2 0.2 0.2 0.2 0.2 0.2 Leveling agent(g) 0.1 0.1 0.1 0.1 0.1 0.1 Anti-sagging agent(g) 0.15 0.15 0.15 0.15 0.15 0.15 Water retaining agent (g) 0.15 0.15 0.15 0.15 0.15 0.15 Hemihydrate gypsum(g) 35 Anhydrous gypsum(g) 35
[0102] 2.2. Preparation method:
[0103] Weigh the raw materials of the above components, stir them evenly in a blender, and then pack them in a moisture-proof and sealed package to prepare the coating. (Note: Store in a dry and sealed environment.)
[0104] When using, add appropriate amount of clean water to the dry powder. The viscosity of the slurry is 14-18s after applying 4 cups. Stir evenly until there are no particles. It can be used for brushing, rolling, or spraying to achieve the appropriate thickness.
[0105] 2.3 Performance test data and results:
[0106] The coatings prepared by formula 1-6 were subjected to performance testing under “1. Technical indicators and test methods of coatings” and the data obtained are shown in Table 4.
[0107] Table 4 Performance test data
[0108]
[0109] From Table 4, we can see that:
[0110] The coating performance obtained by formula 1: the coating surface is smooth and flat, and there is no abnormality in water resistance, alkali resistance, temperature change resistance, and artificial aging resistance. The surface drying time is 1.25h, the contrast ratio is 0.96, the scrub resistance is greater than 2000, the stain resistance is 10.89%, the whiteness is 86.66, the pH is 12, and the evaluation indicators are up to standard; the SEM picture of the coating surface is shown in Figure 4 .
[0111] The coating performance obtained by formula 2: the coating surface has cracks, and the temperature-resistant part is damaged. Compared with formula 1, the construction performance of the product obtained in comparative example 2 is poor;
[0112] The coating performance obtained by formula 3: the coating surface is rough and uneven, and the stain resistance is 40.42%, which exceeds the technical indicators and is unqualified;
[0113] The coating performance obtained by formula 4: the coating surface is rough and uneven, and the stain resistance is 37.87%, which exceeds the technical indicators and is unqualified;
[0114] The coating properties obtained by formula 5: the coating surface is dry-rubbed and powdery, water resistance is damaged, alkali resistance is damaged, temperature resistance is often detached, and stain resistance is 36.38%, which exceeds the technical indicators and is unqualified;
[0115] The coating properties obtained by formula 6: the coating surface is dry-rubbed and powdery, water resistance is broken, alkali resistance is broken, temperature resistance often falls off, and stain resistance is 33.54%, which exceeds the technical indicators and is unqualified.
[0116] In summary, Formulation 1 is the preferred formulation.
[0117] 3 Test 2
[0118] 3.1 The optimal ratio screening test was carried out with the preferred formula 1 obtained under "2 Test 1", and 8 formulas were set up, as shown in Table 5.
[0119] Formulation A - Example 1
[0120] Raw material ratio: 35 parts of dihydrate gypsum, 19 parts of metakaolin, 22 parts of slaked lime, 3 parts of polyvinyl alcohol, 20 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0121] Formulation B - Example 2
[0122] Raw material ratio: 20 parts of dihydrate gypsum, 25 parts of metakaolin, 25 parts of slaked lime, 3 parts of polyvinyl alcohol, 26 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0123] Formulation C - Example 3
[0124] Raw material ratio: 50 parts of dihydrate gypsum, 19 parts of metakaolin, 22 parts of slaked lime, 3 parts of polyvinyl alcohol, 5 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0125] Formulation D - Example 4
[0126] Raw material ratio: 35 parts of dihydrate gypsum, 15 parts of metakaolin, 25 parts of slaked lime, 3 parts of polyvinyl alcohol, 21 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0127] Formulation E - Example 5
[0128] Raw material ratio: 35 parts of dihydrate gypsum, 30 parts of metakaolin, 25 parts of slaked lime, 3 parts of polyvinyl alcohol, 6 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0129] Formulation F - Example 6
[0130] Raw material ratio: 35 parts of dihydrate gypsum, 22 parts of metakaolin, 15 parts of slaked lime, 3 parts of polyvinyl alcohol, 24 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0131] Formulation G - Example 7
[0132] Raw material ratio: 35 parts of dihydrate gypsum, 26 parts of metakaolin, 30 parts of slaked lime, 3 parts of polyvinyl alcohol, 5 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0133] Recipe H
[0134] Raw material ratio: 70 parts of dihydrate gypsum, 10 parts of metakaolin, 11 parts of slaked lime, 3 parts of polyvinyl alcohol, 5 parts of quartz powder, 0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retention agent.
[0135] Table 5 Coating formula screening table
[0136] raw material Recipe A Recipe B Recipe C Recipe D Formulation E Recipe F Formulation G Recipe H Gypsum dihydrate(g) 35 20 50 35 35 35 35 70 Metakaolin(g) 19 25 19 15 30 22 26 10 Slaked lime(g) 22 25 22 25 25 15 30 11 Polyvinyl alcohol (g) 3 3 3 3 3 3 3 3 Quartz powder(g) 20 26 5 21 6 24 5 5 Polycarboxylate high efficiency water reducing agent (g) 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Defoaming agent(g) 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Dispersant(g) 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Leveling agent(g) 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1 Anti-sagging agent(g) 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15 Water retaining agent (g) 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15
[0137] 3.2 Preparation method:
[0138] Weigh the raw materials of the above components, stir them evenly in a blender, and then pack them in a moisture-proof and sealed package to prepare the coating. (Note: Store in a dry and sealed environment.)
[0139] When using, add appropriate amount of clean water to the dry powder. The viscosity of the slurry is 14-18s after applying 4 cups. Stir evenly until there are no particles. It can be used for brushing, rolling, or spraying to achieve the appropriate thickness.
[0140] 3.3 Performance test data and results:
[0141] The coatings prepared by formula AH were subjected to performance testing under “1. Technical indicators and test methods of coatings” and the data obtained are shown in Table 6.
[0142] Table 6 Performance test data of coatings prepared by formula AH
[0143]
[0144] From the results in Table 6, it can be seen that the coating prepared by formula AG has a smooth surface, a surface drying time of less than 2h, a contrast ratio greater than 0.90, a washability of more than 2000 times, and after 5 temperature-resistant cycles, the coating is intact, the stain resistance is less than 15%, and the water resistance, alkali resistance, artificial weather aging resistance and other tests meet the qualified requirements. The coating appearance is intact, and there is no powdering, discoloration, or cracking; the pH of the coating slurry is greater than 10, so there is no need to add an antibacterial agent, and it also has an antibacterial effect. It will not mold or discolor when used on the exterior wall, and the whiteness is greater than 85. No titanium dioxide pigment is required, which can reduce costs. The coating prepared by formula H has a dry-wipe powdery coating, partially damaged water resistance, damaged temperature resistance, and unqualified scrubbing resistance and stain resistance. This shows that when the proportion of dihydrate gypsum used in the raw materials is too large, the performance of the prepared product coating is poor.
[0145] Although the present invention has been described in detail above by means of general description, specific implementation methods and experiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A building coating, characterized in that: The following raw materials are included by weight: 35 parts of dihydrate gypsum, 19 parts of metakaolin, 22 parts of slaked lime, 3 parts of polymer auxiliary film-forming agent, 20 parts of filler, 0.2 parts of high-efficiency water reducing agent, 0.2 parts of defoaming agent, 0.2 parts of dispersant, 0.1 parts of leveling agent, 0.15 parts of anti-sagging agent, and 0.15 parts of water retaining agent; The main component of the dihydrate gypsum is CaSO4·2H2O, with a purity of ≥90%, a whiteness of ≥80%, a fineness of ≥300 mesh, and a moisture content of ≤1.5%; the main components of the metakaolin are silicon dioxide and aluminum oxide, with a whiteness of ≥80%, a fineness of ≥500 mesh, and a moisture content of ≤1.5%; The main component of the slaked lime is Ca(OH)2, with a purity of ≥90%, a whiteness of ≥80%, a fineness of ≥500 meshes, and a moisture content of ≤1.5%.
2. The architectural coating according to claim 1, characterized in that: The polymer auxiliary film-forming agent includes one or more composite powders of water-soluble ethylene / vinyl acetate redispersible latex powder, polyacrylate redispersible latex powder and water-soluble polyvinyl alcohol, with a fineness of ≥100 mesh and a moisture content of ≤2.0%.
3. The architectural coating according to claim 1, characterized in that: The high-efficiency water reducer is a polycarboxylic acid high-efficiency water reducer.
4. The architectural coating according to claim 1, characterized in that: The filler is one or a combination of two or more of quartz powder, talcum powder, wollastonite powder, sericite powder, heavy calcium carbonate powder or diatomaceous earth powder, with a whiteness of ≥80% and a moisture content of ≤1.5%.
Citation Information
Patent Citations
Ecotypic-gypsum-based dry powder coating
CN102173710B
High-strength water-resistant plastering gypsum and producing method thereof
CN101265069A
Exciting agent for improving early performance of slag powder concrete by using desulfurization gypsum and preparation method of exciting agent
CN103241995A